PENGARUH ROE, BVPS, DAN VOLUME PERDAGANGAN SAHAM TERHADAP RETURN SAHAM - Jefri; M Edo S; Destria Kurnianti (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2020)
This research aims to determine the influence of return on equity (ROE), Book Value Per Share (BVPS) and stock trading Volume on the stock return in the coal mining sector company on the Indonesia Stock Exchange (IDX) period from 2013 to 2018. The dependent variables in this study are represented by the stock return, while the independent variables consist of return on equity (ROE), Book Value Per Share (BVPS) and stock trading volumes. The sampling technique in this study is to use the purposive sampling method. Thus, from 22 coal mining companies listed on the Indonesia Stock Exchange during the research period, only 15 companies are eligible for samples. The data obtained is then analyzed by the Data regression Panel. The results showed that out of three independent variables tested against the stock return of a coal mining company, there was one variable that had significant effect on the return of shares, i.e. stock trading volumes, while the ROE and BVPS variables did not affect the return of shares